The Width of Magnetic Ejecta Measured near 1 au: Lessons from STEREO-A Measurements in 2021–2022 - Noé Lugaz; Bin Zhuang; Camilla Scolini; Nada Al-Haddad; Charles J. Farrugia; Réka M. Winslow; Florian Regnault; Christian Möstl; Emma E. Davies; Antoinette B. Galvin (The Astrophysical Journal, 2024)
Coronal mass ejections (CMEs) are large-scale eruptions with a typical radial size at 1 au of 0.21 au but their angular width in interplanetary space is still mostly unknown, especially for the magnetic ejecta (ME) part of the CME. We take advantage of STEREO-A angular separation of 20°–60° from the Sun–Earth line from 2020 October to 2022 August, and perform a two-part study to constrain the angular width of MEs in the ecliptic plane: (a) we study all CMEs that are observed remotely to propagate between the Sun–STEREO-A and the Sun–Earth lines and determine how many impact one or both spacecraft in situ, and (b) we investigate all in situ measurements at STEREO-A or at L1 of CMEs during the same time period to quantify how many are measured by the two spacecraft. A key finding is that out of 21 CMEs propagating within 30° of either spacecraft only four impacted both spacecraft and none provided clean magnetic cloud-like signatures at both spacecraft. Combining the two approaches, we conclude that the typical angular width of an ME at 1 au is ∼20°–30°, or 2–3 times less than often assumed and consistent with a 2:1 elliptical cross section of an ellipsoidal ME. We discuss the consequences of this finding for future multi-spacecraft mission designs and for the coherence of CMEs.